COMBINATION OF BABY EXERCISE AND CLASSICAL MUSIC TOWARDS SLEEP DURATION OF 3 MONTHS BABIES - Sari, Septi Indah Permata; Pandiangan, Tiurlan Benedikta; Harahap, JUraida Roito; Yanti, Yanti (Poltekkes Kemenkes Riau Under Health Ministry Republik Indonesia, 2021)
One important factor that causes babies not to grow optimally because of poor sleep quality. Poor sleep quality causes babies to be fussy and lazy to suckle. All of that can result in decreased body weight and impaired growth, physical development and affect the development of the baby's brain. The purpose of this study was to determine the effect of a combination of baby exercise and classical music to enhancement in baby’s sleep duration. This type of research is quantitative analytic with quasy experimental design. This research was conducted at the Independent Practice of Midwife Siti Julaeha Pekanbaru City in August 2019 to April 2020. The population was 40 babies. A sample of 20 with 10 intervention groups combined infant gymnastics and classical music and 10 music intervention groups alone were taken by consecutive sampling technique. Data analysis used independent t-test with 95% confidence level. The results of this study found an average increase in sleep duration of infants given a combination of baby gymnastics with classical music were 148, 10 minute (SD: 65, 119) and an average increase in sleep duration of infants given classical music 77, 00 minute (SD: 17, 353). There is influence of a combination of baby gymnastics and classical music to an increase in sleep duration of infants aged 3 months (p = 0. 007).